2013
DOI: 10.1530/rep-12-0497
|View full text |Cite
|
Sign up to set email alerts
|

Human testicular peritubular cells: more than meets the eye

Abstract: In healthy men, several layers of inconspicuously flat cells and extracellular matrix (ECM) proteins build the wall of the seminiferous tubules. The cells of this wall, peritubular cells, are not well characterized. They are smooth-muscle-like and contractile and transport immotile sperm, a function important for male fertility. However, their full functional importance, especially their potential contribution to the paracrine regulation of the male gonad, is unknown. In men with impaired spermatogenesis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 67 publications
3
118
1
1
Order By: Relevance
“…MPCs secrete numerous cytokines, including pro-inflammatory and anti-inflammatory factors, under physiological and inflammatory conditions. 22,68 The functions of MPCs that are involved in regulating testicular immunity are worthy of further investigation.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…MPCs secrete numerous cytokines, including pro-inflammatory and anti-inflammatory factors, under physiological and inflammatory conditions. 22,68 The functions of MPCs that are involved in regulating testicular immunity are worthy of further investigation.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…For instance, in rodents, the tubular wall is composed of a single cell layer and a tiny extracellular matrix. However, in the human testis, the seminiferous tubule wall is composed of the following components: an internal acellular basal membrane adjacent to the germinal epithelium containing collagen fibers, laminin, glycoproteins, and hyaluronic acid; a middle cellular zone made of spindle-shaped and contractile cells (called myoid cells or myofibroblasts); and an external cellular zone consisting of collagen-producing fibroblasts (Pop et al 2011, Mayerhofer 2013. Disturbances in testicular function and decreased or no spermatogenic activity are associated with a thickening of the seminiferous tubule wall, which becomes fibrotically remodeled.…”
Section: Cox and Pgs In The Seminiferous Tubule Wallmentioning
confidence: 99%
“…Disturbances in testicular function and decreased or no spermatogenic activity are associated with a thickening of the seminiferous tubule wall, which becomes fibrotically remodeled. Fibroblasts, together with smooth muscle cells, mediate tissue fibrosis and collagen deposition (Mayerhofer 2013). This frequent change is observed irrespective of the causes of male infertility and is regarded as a hallmark of male infertility (Frungieri et al 2002a, Weinbauer et al 2010.…”
Section: Cox and Pgs In The Seminiferous Tubule Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their structural function, these cells behave as active agents in the regulation of testicular homeostasis, through the secretion of different factors, including ECM components (Ailenberg et al, 1988;Dıez-Torre et al, 2011). For instance, it has been shown that these smooth muscle-like cells play important roles in human male fertility, in the paracrine regulation of the male gonad and in the establishment of the spermatogonial stem cell (SSC) niche (Albrecht et al, 2006;Mayerhofer, 2013;Flenkenthaler et al, 2014). Nevertheless, the potential of PTCs as a part of the TGCT together with the tumor reactive stroma, to be a source of proinvasive factors, remains unknown.…”
Section: Introductionmentioning
confidence: 99%